From Responsible Research and Innovation to responsibility by design. Issue 2 (4th May 2021) - Stahl, Bernd Carsten; Akintoye, Simisola; Bitsch, Lise; Bringedal, Berit; Eke, Damian; Farisco, Michele; Grasenick, Karin; Guerrero, Manuel; Knight, William; Leach, Tonii; Nyholm, Sven; Ogoh, George; et al.
ABSTRACT: Drawing on more than eight years working to implement Responsible Research and Innovation (RRI) in the Human Brain Project, a large EU-funded research project that brings together neuroscience, computing, social sciences, and the humanities, and one of the largest investments in RRI in one project, this article offers insights on RRI and explores its possible future. We focus on the question of how RRI can have long-lasting impact and persist beyond the time horizon of funded projects. For this purpose, we suggest the concept of 'responsibility by design' which is intended to encapsulate the idea of embedding RRI in research and innovation in a way that makes it part of the fabric of the resulting outcomes, in our case, a distributed European Research Infrastructure.